RELATIONSHIP OF FACIAL SKELETAL VERTICAL DIMENSION AND PALATAL LENGTH TO MIDPALATAL SUTURE - Caitlin Reva Isman; Harryanto Wijaya; Sariyani Pancasari Audry Arifin (Fakultas Kedokteran Gigi Unjani, 2026)
Malocclusion can significantly impact facial aesthetics, oral function, and quality of life, with cases often involving maxillary constriction treated by rapid palatal expansion (RPE). Treatment success depends on the evaluation of midpalatal suture maturation that is often done through CBCT, whose routine use is limited by concerns related to radiation exposure, cost, and accessibility. This study aims to evaluate the relationship between facial skeletal vertical dimension and palatal length with midpalatal suture maturation as potential noninvasive clinical indicators. An analytical observational study with a cross-sectional design was conducted using cephalography and CBCT images from 47 subjects aged 8–19 years. The facial skeletal vertical dimension was determined using the SN–MP parameter, palatal length was measured by linear cephalometric analysis, and midpalatal suture maturation was assessed using the Angelieri method. Fisher’s exact test and t-test were used for statistical analysis. The results showed no significant relationship between facial skeletal vertical dimension (p=0.197) or palatal length (p=0.477) and midpalatal suture maturation. In conclusion, facial skeletal vertical dimension and palatal length does not have a significant relationship with midpalatal suture maturation and should not be used as predictive clinical parameters. DOI : 10.54052/jhds.v6n1.p11-24